The Effect of Financial Literacy and Lifestyle on Financial Management Behavior with Self-Efficacy as a Mediation Variable: A Study of Young Workforce in Tuban Regency - Rifa Fatra Yahya Masruroh; Farahiyah Sartika (Economics and Business Journal (ECBIS), 2026)
This study aims to analyze the influence of financial literacy and lifestyle on financial management behavior, with self-efficacy as a mediating variable among young workers in Tuban Regency. This study employed a quantitative approach involving 160 respondents, and the data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) through SmartPLS 3. The results indicate that financial literacy, lifestyle, and self-efficacy have significant effects on financial management behavior. Financial literacy also significantly influences self-efficacy, while lifestyle does not have a significant effect on self-efficacy. Furthermore, self-efficacy is proven to mediate the relationship between financial literacy and financial management behavior, but it does not mediate the relationship between lifestyle and financial management behavior